Diagnostic and prognostic value of combined detection of serum Tg, IFN - γ and TgAb in thyroid adenoma - Min, Sun; Xiaxing, Liu; Yu, Bai; Yinghua, An; Yaoni, Li; Jinbo, Wang (Cellular and Molecular Biology, 2022)
This study aimed to explore the value of combined detection of serum thyroglobulin (Tg), interferon - γ (IFN - γ) and thyroglobulin antibody (TgAb) in the diagnosis and prognosis of thyroid adenoma (TA). For this purpose, 100 patients with TA in our hospital from January 2017 to December 2020 were selected as the observation group, and they were divided into good prognosis group (83 cases) and poor prognosis group (17 cases) according to the surgical treatment; another 50 healthy people who received physical examination in our hospital. The levels of serum Tg, IFN - γ and TgAb in each group were detected and compared; the diagnostic and prognostic value of combined detection of serum Tg, IFN - γ and TgAb in thyroid adenoma were analyzed. Results showed that compared with the control group, the levels of Tg and TgAb in the observation group were significantly increased, and the levels of IFN - γ were significantly decreased (P < 0.05); compared with the poor prognosis group, the levels of Tg and TgAb in the good prognosis group were significantly decreased, and the levels of IFN - γ were significantly increased (P < 0.05); The area under curve (AUC) of the combined detection of serum Tg, IFN-γ and TgAb for TA diagnosis and prognosis assessment was significantly higher than the value detected by a single indicator. In general, the combined detection of serum Tg, IFN - γ and TgAb has high diagnostic and prognostic value for TA, and has high clinical reference value.